Desafios da inovação no jornalismo: a migração do modelo impresso ao digital no jornal Cinform - Silva, Gilson Sousa (2019)
The research deals with aspects of the transformations of the newspaper Cinform, from Aracaju (SE), which in 2017 migrated from the printed to the digital platform. With this, it seeks to answer what types of innovation in journalism practice occurred in this migration process. From the literature on innovation, this study contemplated the analysis of innovative processes and products, be it in the aspect of technologies, organizational forms, market, and also marketing. In this sense, in the case of Cinform, there are innovations in the product, when publishing editions of the digital newspaper with the PDF extension. However, as for the production process of the newspaper, there is a hybrid practice in its form of investigate, editing and disseminating news, contemplating models of journalistic production of the past that do not fit the concept of innovation. Furthermore, the process makes the business model of the journalistic organization unsafe and unsustainable. It also affects the profession of journalist, modifying routines, spaces and the way to produce news.